The ultimate hitchhiker's guide to the galaxy - Adams, Douglas, 1952-2001. (New York : Ballantine Books, 2002)
A collection of five novels by Douglas Adams that follow the adventures of Arthur Dent as he travels the universe, and includes a bonus short story.
The hitchhiker's guide to the galaxy -- The restaurant at the end of the universe -- Life, the universe and everything -- So long, and thanks for all the fish -- Young Zaphod plays it safe -- Mostly harmless.
Adult
Keywords: Dent, Arthur (Fictitious character) -- Fiction; Prefect, Ford (Fictitious character) -- Fiction; Voyages, Imaginary -- Fiction; Dent, Arthur (Fictional character) -- Fiction; Imaginary voyages -- Fiction; Prefect, Ford (Fictional character) -- Fiction; Science fiction